Methane occurrence and origin in Dutch groundwater: from shallow aquifers to deep reservoirs - Gilian Schout; Jasper Griffioen; Niels Hartog; Hans G.M. Eggenkamp; Dirk Gijsbert Cirkel (Netherlands Journal of Geosciences)
Methane is a common constituent of groundwater with multiple possible origins. Elevated methane concentrations may also result from anthropogenically induced pathways between the deep and shallow subsurface caused by oil and gas production. A baseline characterisation of methane occurrence and origin in the subsurface of the Netherlands was made using a large set of methane concentrations in shallow groundwater (n = 12,219, up to 500 mbgs). Additionally, targeted sampling (n = 40) was carried out in (1) the shallow aquifers at locations where the presence of thermogenic methane was deemed most probable, such as above faults and known gas reservoirs, (2) deep groundwater aquifers below the depth of Neogene and Paleogene marine clays that form the hydrogeological base in the country and (3) geothermal formation waters at 1640–2625 mbgs. Median methane concentrations in shallow aquifers are relatively high from an international perspective (0.2 mg L−1). The highest methane concentrations (up to 120 mg L−1) are attributed to reactive organic matter in Holocene deposits and Pleistocene marine and glacial formations. However, elevated concentrations are also found at greater depth (100–160 m bgs) in Pleistocene aquifers in the eastern and southern inland areas of the Netherlands. Isotopic evidence and gas composition of naturally occurring methane indicate that methane in the targeted samples from shallow aquifers was of biogenic origin, and that methanogenesis predominantly occurs via CO2 reduction. Only trace amounts of methane (<0.2 mg L−1) were observed in the deep groundwater aquifers. A combination of methane and ethane isotopic composition showed that this methane consists of varying fractions of both biogenic and thermogenic origin. Methane in the geothermal reservoirs has an oil associated thermogenic origin. Overall, these findings highlight that future observations of thermogenic methane in Dutch shallow groundwater (post-Paleogene) are most probably linked to anthropogenically induced connections with the deep subsurface.